Penerapan Teknik Rumpang dalam Pembelajaran Demokrasi: Membangun Pola Pikir Demokratis Siswa Fase B Sekolah Dasar berdasarkan Teori Konstruktivisme Sosial - Ratna Fitria; Warlim; Aang Supriatna; Vini Agustiani H (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the cloze technique in democratic learning to foster democratic mindsets among Phase B elementary school students (grades 3-4) grounded in Vygotsky's social constructivism theory. The research employed Classroom Action Research (CAR) with two cycles involving 25 third-grade students at SDN Kabupaten Bandung Barat. Data collection utilized democratic attitude observation sheets, teacher activity observation sheets, and field notes. The findings revealed a significant progressive improvement in students' democratic dispositions, with mean scores increasing from 41.2 (pre-cycle) to 65.8 (cycle I), reaching 82.4 (cycle II), with 88% of students achieving the